2019
DOI: 10.13060/1214438x.2019.1.17.497
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Children and Youth to Railway Trespassing

Abstract: Tento článek byl vytvořen za finanční podpory Ministerstva školství, mládeže a tělovýchovy v rámci programu Národní program udržitelnosti I, projektu Dopravní VaV centrum (LO1610) na výzkumné infrastruktuře pořízené z Operačního programu Výzkum a vývoj pro inovace (CZ.1.05/2. 1. 00/03.0064).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A study in the Czech Republic has shown that adults can have a negative influence on young people aged 11-16 years when it comes to trespassing. Peer influence also plays a major role, as there are no consequences for bad behaviour [59]. Trespassing on railway tracks is mainly due to human factors [60].…”
Section: Trespasser Profile and Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in the Czech Republic has shown that adults can have a negative influence on young people aged 11-16 years when it comes to trespassing. Peer influence also plays a major role, as there are no consequences for bad behaviour [59]. Trespassing on railway tracks is mainly due to human factors [60].…”
Section: Trespasser Profile and Behaviourmentioning
confidence: 99%
“…The lack of safety knowledge is also present among young people aged 11 to 16. Young people are aware of the dangers of their actions, but they have limited ability to assess the risk and have various misconceptions regarding illegally crossing railway tracks [59]. The question is how many illegal crossings (trespassing) are due to a lack of knowledge and how much is intentional.…”
Section: Motivation For and General Knowledge Of Railway Trespassingmentioning
confidence: 99%